Екологічні уподобання афілофороїдних грибів Національного природного парку «Мезинський» - Ачкасов, Д.О. (Львів : Інститут екології Карпат НАН України, 2021)
Data about the biodiversity of aphylophoroid fungi from the territory of Mezynsky National Nature Park and their substrate preference are given below. The distribution of species and specimens by wood plants, as well as size classes and stages of wood destruction are indicated
Achkasov D. Ecological preferences of Aphyllophoroid fungi of the National Nature Park “Mezynsky”
Keywords: гриби; біорізноманіття; ксилотрофи; національний природний парк; екологія